On the value of accurate demand information in public-private emergency collaborations - Florian Diehlmann; Miriam Klein; Marcus Wiens; Markus Lüttenberg; Frank Schultmann (Karlsruhe Institute of Technology (KIT), Institute for Industrial Production (IIP), 2020)
In cases where the private sector struggles to cope with the impact of a disaster, authorities try to reduce the burden on the population and set up supply chains to distribute essential goods. Therefore, they estimate demand and location of the affected people and open points of distribution to supply goods from, e.g. public buildings or sports facilities. However, the location of these points of distribution depends heavily on accurate demand estimations. Combined with a high time pressure that prevents the collection of detailed data, inefficient decisions result. However, these decisions improve significantly if private actors share their market knowledge. Since this information is strictly confidential for companies and at the same time requires a lot of coordination effort from public actors to acquire, the quantification of the benefits of the collaboration is important for both sides. Moreover, the time at which the information is received and the way the information is utilized regarding different intervention intensities is supposed to be crucial. Therefore, we develop a framework to quantify the consequences of shared information for both actors and apply it to a case study for a tap water contamination in the city of Berlin. We highlight that both actors benefit from the collaboration and that the time the information is received has a comparably low effect on the total supply. Moreover, we show that private actors can reduce the impact of market interventions on their processes significantly by actively collaborating with authorities.
Keywords: 330; crisis management; humanitarian logistics; points of distribution; information; preparedness; facility location planning